Microbicidal Activity of Extract Larrea tridentata (Sessé and Moc. ex DC.) Coville on Pseudomonas syringae Van Hall and Botrytis cinerea Pers - Diego Rivera-Escareño; Jorge Cadena-Iñiguez; Dalia Abigail García-Flores; Gerardo Loera-Alvarado; Lizeth Aguilar-Galaviz; María Azucena Ortega-Amaro (Microorganisms)
Due to their secondary metabolite content, plant extracts are an alternative method for controlling pathogenic organisms in agriculture and post-harvest operations. Botrytis cinerea and Pseudomonas syringae are among the causative agents of diseases and losses in agricultural production. The species Larrea tridentata is abundant in the arid and semi-arid zones of Mexico and has no defined use; however, it contains secondary metabolites with microbicidal potential that could aid in biological control and enhance its harvest status. Growth inhibition (halo) of B. cinerea and P. syringae was evaluated by applying alcoholic extract of L. tridentata leaves at doses of 50, 100, 250, 500, 750, 1000, and 2000 µg mL−1 in vitro, using poisoned medium and potato dextrose agar for the fungus and the agar well method for the bacteria, in a completely randomized design with five replicates. The flavonoids quercetin, apigenin, narigenin, kaempferol, and galangin were identified as possible agents of microbicidal activity. The extract inhibited the growth of B. cinerea from 100 µg mL−1 and completely inhibited it with 1000 and 2000 µg mL−1. For P. syringae, inhibition was observed from 250 µg mL−1, demonstrating that the higher the concentration, the greater the growth inhibitory effect. The secondary metabolite content of the L. tridentata extract is sufficient to have an impact on microorganisms with economic impact in agriculture.